2008
DOI: 10.1080/00036840600892910
|View full text |Cite
|
Sign up to set email alerts
|

News and volatility of food prices

Abstract: Financial markets exhibit an asymmetric news effect with unexpected low prices generating more price volatility than 'news' of high prices. The present study examines US food markets for such asymmetric news effects. Analysis of 25 years of monthly data for 45 retail food items shows that price news destabilizes about a third of the markets with unexpected price increases more destabilizing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 30 publications
3
20
1
1
Order By: Relevance
“…It seemed that EGARCH model is the best prediction model for all commodities, except CPO. The predictability of EGARCH Model in predicting the returns volatility of Indonesia exported agricultural commodities is supported by the studies of Swaray (2002) and Zheng et al (2008). TGARCH model is found as the best model in predicting the returns volatility of CPO.…”
Section: Table 10 the Results Of Garch Construction Process For Blacmentioning
confidence: 63%
See 1 more Smart Citation
“…It seemed that EGARCH model is the best prediction model for all commodities, except CPO. The predictability of EGARCH Model in predicting the returns volatility of Indonesia exported agricultural commodities is supported by the studies of Swaray (2002) and Zheng et al (2008). TGARCH model is found as the best model in predicting the returns volatility of CPO.…”
Section: Table 10 the Results Of Garch Construction Process For Blacmentioning
confidence: 63%
“…Many researchers have employed and extended the ARCH/GARCH methodology to examine various commodities price volatility issues. For example, Alom et al (2010);Sumaryanto (2009);O"Connor et al (2009);Zheng et al (2008); Rezitis (2003, 2011);Yang et al (2001);and Beck (2001), theyapplied GARCHtype models to analyze the price volatility of agricultural products. Some empirical studies reported the existence of price volatility in futures prices and spot prices of some commodities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Pindyck(2004) pointed out that changes in commodity prices can influence the total cost of production as well as the opportunity cost of producing commodities currently rather than later. It has also been argued that price volatility reduces welfare and competition by increasing consumer search costs (Zheng, Kinnucan, & Thompson, 2008). In the same line, Apergis and Rezitis(2003b) noted down that price volatility leads both producers and consumers to uncertainty and risk and thus volatility of commodity prices has been studied to some extent.…”
Section: Introductionmentioning
confidence: 91%
“…They used univariate EGARCH models to check volatility spillover and provided evidence of volatility spillovers in agricultural markets. Zheng et al (2008) studied time varying volatility of US food consumer prices using Exponential GARCH models and news impact curves.…”
Section: Introductionmentioning
confidence: 99%
“…This category is represented by the papers of Chavas and Mehta (2004), Zheng et al (2008), Mehta and Chavas (2008), Serra (2011 and Rezitis (2012). This category is also dominated by studies for the US and Greek markets, but shows some variations in the products studied.…”
Section: Price Volatility Transmission In Food Supply Chainsmentioning
confidence: 99%